2009
DOI: 10.1021/ic9010828
|View full text |Cite
|
Sign up to set email alerts
|

Effective Control of Ligation and Geometric Isomerism: Direct Comparison of Steric Properties Associated with Bis-mesityl and Bis-diisopropylphenyl m-Terphenyl Isocyanides

Abstract: A synthetic procedure for the sterically encumbered m-terphenyl isocyanide CNAr(Dipp2) (Dipp = 2,6-diisopropylphenyl) is presented. In comparison to the less encumbering m-terphenyl isocyanide ligand CNAr(Mes2), the steric attributes of the flanking Dipp groups effectively control the extent of CNAr(Dipp2) ligation to monovalent Cu and Ag centers and zero-valent Mo centers. Direct structural comparisons of Cu(I) and Ag(I) complexes of both CNAr(Dipp2) and CNAr(Mes2) are made. It was found that only two CNAr(Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
91
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 60 publications
(98 citation statements)
references
References 101 publications
6
91
1
Order By: Relevance
“…26 For these latter metals, CNAr Dipp2 was shown to very effectively discourage the association of a third isocyanide ligand. 26 In the present case of Ni(0), it is demonstrated that CNAr Dipp2 can indeed form a stable, homoleptic tris-isocyanide complex and then discourage ligation of a fourth isocyanide ligand.…”
Section: ' Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…26 For these latter metals, CNAr Dipp2 was shown to very effectively discourage the association of a third isocyanide ligand. 26 In the present case of Ni(0), it is demonstrated that CNAr Dipp2 can indeed form a stable, homoleptic tris-isocyanide complex and then discourage ligation of a fourth isocyanide ligand.…”
Section: ' Concluding Remarksmentioning
confidence: 99%
“…26 For these latter metals, CNAr Dipp2 was shown to very effectively discourage the association of a third isocyanide ligand. 26 In the present case of Ni(0), it is demonstrated that CNAr Dipp2 can indeed form a stable, homoleptic tris-isocyanide complex and then discourage ligation of a fourth isocyanide ligand. Importantly, this property enabled the synthesis of Ni-(CNAr Dipp2 ) 3 without the need for a coordination-site protection as had been employed previously for the synthesis of the dimesityl derivative, Ni(CNAr Mes2 ) 3 .…”
Section: ' Concluding Remarksmentioning
confidence: 99%
“…[32][33][34] In addition, in our studies on Group 6m etal complexes featuring two CNAr Dipp2 ligands,w eh ad previously shown that the steric encumbrance of these isocyanides enforces am utually trans orientation through multiple redox transformations of the metal center. [18,19] We believe that to relieve steric pressure,this constrained, trans isocyanide environment around the metal center shifts the equilibrium between the two C-alkenyl insertion products to the configuration favoring production of the (E)-b-vinylstannane isomer ( Figure 2). This argument is analogous to that made for regioselective (E)-b-vinylstannane formation using palladium and encumbering phosphine ligands, [15] with the added feature that two cis-oriented ligands provide steric pressure in this sixcoordinate Mo system.…”
mentioning
confidence: 99%
“…Additionally, investigations into the one-electron activation chemistry of [Mn(CO) 5Àn L n ]s pecies with small molecule substrates are limited. [22,23] Thesterically encumbering nature of these isocyanidel igands effectively prevents the formation of MnÀMn single bonds,thus rendering this 17e À radical both isolable in the solid state and persistent in solution. [19][20][21] Accordingly,successful strategies leading to the kinetic stabilization and isolation of such [MnL 5 ] monoradicals,while explicitly preventing the formation of the common Mn À Mn single-bond motif,a re of importance in these processes.F urthermore,a ccess to long-lived [MnL 5 ] monoradicals offers ap otential avenue for the development of selective,well-defined metal-mediated one-electron transformations.H erein we describe the isolation, structure,a nd spectroscopic features of the neutral monoradical [Mn-(CO) 3 (CNAr Dipp2 ) 2 ]( Ar Dipp2 = 2,6-(2,6-(iPr) 2 C 6 H 3 ) 2 C 6 H 3 )f eaturing two m-terphenyl isocyanide ligands.…”
mentioning
confidence: 99%